Exigências dietéticas de arginina e isoleucina para tilápias do Nilo - Neu, Dacley Hertes (2013)
Two studies were carried out to determine the dietary arginine and isoleucine requeriment for juvenile Nile tilapia through growth performance, biochemical and hematological parameters and muscle growth. In both experiments, the fish were fed ad libitum with extruded diets. In the first experiment, which lasting 85 days, three-hundred Nile tilapia juveniles (2.95±0.79 g) were distributed into 20 fiberglass aquaria (500-L each). Five extruded diets, isonitrogenous (28.0% crude protein) and isocaloric (3160 kcal.kg-1 digestible energy), with 0.95; 1.10; 1.25; 1.40 and 1.55% of arginine were elaborated. Based on second order regression analysis, the best results of weight gain, feed conversion rate, protein efficiency rate and protein retention were estimated by fish fed diets containing 1.36; 1.34; 1.36 and 1.37% of arginine, respectively. The maximum amino acid body retention was estimated in fish fed diets containing 1.31 to 1.37% of arginine. In fish fed 0.95% of arginine the muscle growth occurred mainly, by hyperplasia, while fish fed 1.1 to 1.55% arginine showed decreased in the time of hyperplasia and promoted initialization of hypertrophy. Fish fed with arginine levels did not show differences on body crude protein, fat and amino acid composition, biochemical and hematological parameters. A dietary requirement of 1.36% arginine was determined for juvenile Nile tilapia. In the second study, three-hundred Nile tilapia juveniles (18.09±0.11 g) were distributed into 20 fiberglass aquaria of 500-L each. Five extruded diets, isonitrogenous (28.0 % crude protein) and isocaloric (3160 kcal.kg-1 digestible energy) with 0.70; 0.81; 0.93; 1.05 and 1.17 % of isoleucine were elaborated. No significant difference (P>0.05) on growth performance, hematological and biochemical parameters, whole body composition, amino acid in body composition and muscle growth were observed. The body amino acid retention had an effect only for body isoleucine that decreased according to increasing dietary isoleucine levels. It wasconcluded that diet containing 0.70 % isoleucine meets the requirement for Nile tilapia juveniles.